ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN PRODUK HANDPHONE MEREK SAMSUNG - Lulu Yuliarti, 07.05.51.0105; Widyasari, Suzy (Students Journal of Economic and Management, 2012)
Handphone is one of the communication tools used by the public, including the Samsung brand mobile phone. Samsung is one of the mobile phone product reliability has been recognized by the society are expected to meet the desires and needs of the growing competition in line with a cell phone with a variety of other brands with marketing strategies that are not as good. On every purchase of goods, there are several factors that consumer decision to purchase, other products, pricing, promotion, distribution and social factors are reflected in the reference group, family, role and social status. The purpose of this study was to analyze the influence of product, price, promotion, distribution and social factors on purchase decision on Samsung mobile phone brand Stikubank Semarang University student. There are five hypotheses were tested in this study. The fourth hypotheses tested the effect of each variable, namely product, price, promotion, distribution and social factors partially on purchasing decisions. The fifth hypothesis tested the effect five variables as simultanly on purchase decisions. Type of data used in this study is the primary data is data obtained directly from the original source. While the techniques used for data collection used a questionnaire to ask a number of written questions used to obtain information and respondents. The population in this study were students of Faculty of Economics, University of Stikubank Semarang. The amount of sample used in this study is 100 people. Purposive sampling technique sampling. Test equipment used in this study using the Analysis Factor test validity, reliability testing using Cronbach alpha and test hypotheses using multiple linear regression. The analysis concluded that: the product has positive and significant impact on buying decisions, prices have a positive and significant impact on purchasing decisions, promotion of a positive and significant influence on purchase decisions, the distribution has positive and significant impact on purchasing decisions, social factors influence positive and significant impact on purchasing decisions, product, price, promotion, distribution and social factors together have a positive and significant impact on purchasing decisionsKey words: Product, Price, Promotion, Distribution, Social Factors and Purchasing Decisions